PENGARUH MEDIA VIDEO TERHADAP HASIL BELAJAR SISWA KELAS X IPS SMA NEGERI 2 PONTIANAK - Tita Wahyuni; Budiman Tampubolon; Parijo Parijo (Universitas Tanjungpura, 2019)
AbstractThis research aimed to analyze the extent of the influence of the use of video media learning geography learning material on hydrosphere dynamics of hydrosphere and its impact on the lives of student learning outcomes against X-grade IPS School Intermediate A bag Interior 2 Pontianak. The research method used was the method of experiments with forms of research quaisy experiment design with nonequivalent control group design. The population of this research was to grade X IPS high school 2 Pontianak. The sample in this research was the class. The technique of sampling probability sampling was used. Data collecting tool in the form of test results of student learning that was a matter of objective amounted to 30 items. Calculation based on the results of the research of the control class and classroom experiments obtained thitung of 3.089 and ttabel with a = 5% and dk = 1.998 was 65. Thus thitung (3.089) > ttabel (1.998), thus Ha was received. So, it can be concluded that there was an influence of the use of video media on learning the geography of the hydrosphere learning towards a learning outcomes grade X IPS high school 2 Pontianak. Based on the results of the calculation of Effect Size obtained ICE of 0.81 (criteria). This means learning by using learning video media hydrosphere on learning geography gives the influence to student learning outcomes grade X IPS high school 2 Pontianak.Keywords: Learning Results, Media Influence Learning The Hydrosphere, Video